From the Front Lines Software Development Amidst the Whiz of Silver Bullets. - Bell, Alex E. (Communications of the ACM, 2008)
The author views with skepticism the proliferation of technological advances in software development that are often assumed to have implicit value in themselves. From object orientation to high-level software languages to integrated development environments, such "silver bullets" have been promoted by enthusiasts as innovative solutions, even when they merely reframe existing problems in new terms. The author specifically cites XML, UML, and Web services as current examples of supposedly all-purpose technologies.